Are there gender differences in severity of ankylosing spondylitis? Results from the PSOAS cohort. Issue 5 (24th November 2006) - Lee, Wonuk; Reveille, John D; Davis, John C; Learch, Thomas J; Ward, Michael M; Weisman, Michael H
Abstract : Objective: To examine the clinical and radiographic features in men and women in the Prospective Study of Outcomes in Ankylosing Spondylitis cohort, a large well-defined cross-sectional study of patients with AS, in order to understand the influence of gender in determining the severity of ankylosing spondylitis. Methods: Extensive clinical assessments and spine radiographs were performed in 302 men and 100 women with AS of ⩾20 years duration. Radiographs were scored using the Bath Ankylosing Spondylitis Radiographic Index Spine (BASRI-spine) score (range 2–12). Functional impairment was measured by the Bath Ankylosing Spondylitis Functional Index (BASFI) and the Health Assessment Questionnaire for the Spondyloarthropathies (HAQ-S). Results: Radiographic severity was worse among men. The unadjusted median BASRI-spine score for men was 10, compared with 6.5 for women (p<0.001). Functional disability, as measured by the BASFI and HAQ-S, was not different between men and women. However, after adjusting for radiographic spinal damage, women were found to report worse functioning than men at any given level of radiographic damage. Women had a slightly earlier age of disease onset; however, disease duration was identical in both groups. Women more frequently reported family histories of AS in first-degree relatives and were more likely to be treated with intra-articular steroids, sulphasalazine and prednisone. Conclusions: Among patients with longstanding AS, men have more severe radiographic changes; findings of treatment differences suggest that women may have more peripheral arthritis. At any given level of radiographic damage, self-reported functional limitations were worse for women.